Customer expectation of halal certification at kopitiam in Shah Alam / Muhamad Zaki Aziz and Hazirah Hamid - Aziz, Muhamad Zaki; Hamid, Hazirah (2013)
The importance of Halal food certification has increased as the number of Muslim populations boost. The use of halal certification is very important in helping customers especially Muslim in selecting the halal restaurant especially kopitiam. This study empirically investigates the halal certification attributes that associated with expectation among the customers at the Hailam Kopitiam, Pappa Rich Kopitiam and Killiney Kopitiam in Shah Alam, Selangor. Using the quantitative approach, the experiences of four hundred and eight (408) customers were tapped. Through a series of descriptive and inferential statistic some meaningful insights on the issues of interest were obtained. Findings clearly revealed that trust, food quality and hygiene and safety are recognized as contributory factors that influenced customer expectation. Among these, food quality dimensions were to be the most important thing in customer expectation compared to trust and hygiene and safety. The result of this study has given some implications not only for the customers, but also for the business and managers of the kopitiam as a whole.